Sex-specific stress and biobehavioral responses to human experimenters in rats - Faraji, Jamshid; Ambeskovic, Mirela; Sauter, Nevyn; Toly, Jaxson; Whitten, Kera; Lopes, Nayara Antunes; Olson, David M.; Metz, Gerlinde A. S. (Frontiers in Neuroscience, 2022)
Important factors influencing the outcome of animal experiments in preclinical research are often overlooked. In the current study, the reaction of female and male rats towards the biological sex of a human experimenter was investigated in terms of anxiety-like behaviours and physiological stress responses, as measured by infrared (IR) thermography, circulating corticosterone and oxytocin levels. Female rats displayed consistently exacerbated anxiety-related behaviours along with elevated body surface temperature during repeated exposure to male experimenters. Experimental stress further intensified thermal responses to a male experimenter, especially in female rats. The behavioural responses to a male experimenter in females were associated with higher circulating corticosterone and lower oxytocin levels. Similar responses were induced by a T-shirt worn by a human male. The findings suggest that psychophysiological responses of female rats to a male experimenter are influenced by olfactory cues. The results emphasize the need to not only consider sex differences in experimental animals, but also standardize and report the experimenter’s biological sex to avoid ambiguity in the generation and interpretation of results.